2018
DOI: 10.2147/oajsm.s150596
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training versus moderate-intensity continuous training within cardiac rehabilitation: a systematic review and meta-analysis

Abstract: Background: Aerobic capacity has been shown to be inversely proportionate to cardiovascular mortality and morbidity and there is growing evidence that high-intensity interval training (HIIT) appears to be more effective than moderate-intensity continuous training (MICT) in improving cardiorespiratory fitness within the cardiac population. Previously published systematic reviews in cardiovascular disease have neither investigated the effect that the number of weeks of intervention has on cardiorespiratory fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
0
46

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 49 publications
9
145
0
46
Order By: Relevance
“…However, in our study only patients in the HIIT group showed a substantial trueV˙O2peak improvement and reached a normal age‐predicted trueV˙O2peak after completion of the program with the identical level of exhaustion (ie, RER) as compared to the usual care group. This improvement is consistent with existing data in the identical population and with the biggest and latest of numerous meta‐analyses comparing HIIT and MICET in a population of CHD patients who reported the most pronounced improvements with HIIT after 7 to 12 weeks of training . The finding that trueV˙O2 at the VT1 improved only in the HIIT group indicates an improvement in muscular function as a result of structured exercise training and is plausible …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, in our study only patients in the HIIT group showed a substantial trueV˙O2peak improvement and reached a normal age‐predicted trueV˙O2peak after completion of the program with the identical level of exhaustion (ie, RER) as compared to the usual care group. This improvement is consistent with existing data in the identical population and with the biggest and latest of numerous meta‐analyses comparing HIIT and MICET in a population of CHD patients who reported the most pronounced improvements with HIIT after 7 to 12 weeks of training . The finding that trueV˙O2 at the VT1 improved only in the HIIT group indicates an improvement in muscular function as a result of structured exercise training and is plausible …”
Section: Discussionsupporting
confidence: 90%
“…MICET in a population of CHD patients who reported the most pronounced improvements with HIIT after 7 to 12 weeks of training. 16,32 The finding that _ VO 2 at the VT1 improved only in the HIIT group indicates an improvement in muscular function as a result of structured exercise training and is plausible. 33 LVEF, left ventricular ejection fraction; LVEDVi, left ventricular end-diastolic volume index; LVMI, left ventricular mass index; SR, strain rate; Peak A, peak late mitral inflow velocity; Peak E, peak early mitral inflow velocity; TDI-e 0 lateral, tissue Doppler imaging-derived peak early diastolic lateral mitral annulus velocity; TDI-e 0 septal, tissue Doppler imaging-derived peak early diastolic septal mitral annulus velocity; E/e 0 , peak early mitral inflow velocity to peak early diastolic mitral annulus velocity ratio.…”
Section: Echocardiographic Parametersmentioning
confidence: 93%
See 2 more Smart Citations
“…Due to underlying medical comorbidities and functional limitations of individuals post stroke, task performance safety in terms of physical and physiological events may be a concern during HIIT. However, it has been shown that HIIT is a safe and effective intervention in a variety of clinical populations, including those with cardiovascular and respiratory diseases …”
Section: Introductionmentioning
confidence: 99%